シラセ トウサイ ヨウ コンテナ ジッケンシツ ノ ガイヨウ - 和田, 誠; ワダ, マコト; 古賀, 聖治; コガ, セイジ; 野村, 大樹; ノムラ, ダイキ; 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Wada, Makoto; Koga, Seizi; et al. (2011)
P(論文) 2009年に就航した新「しらせ」には,改造した20 ftコンテナを船上実験室として搭載するスペースが確保された.第51次日本南極地域観測隊では,このコンテナ実験室の内部に大気中の硫化ジメチル濃度を測定するためのプロトン移動反応質量分析計を収納し,観測を実施した.本稿では,コンテナ実験室の概要と今後改良すべき点等について報告する. A portable laboratory, made from a modified 20 feet-long cargo container,was newly installed on the observation deck of the RV Shirase on her maiden voyage to the Antarctic during 2009-2010. The laboratory was used to measure the concentrations of volatile organic compounds (e.g., dimethyle sulfides) in samples of air collected from above the sea and the sea ice, using a proton transfer reaction-mass spectrometer (PTR-MS). This paper describes the laboratory and notes several problems to be overcome in terms of its use. Errata_1 | http://id.nii.ac.jp/1291/00009628/ Errata_2 | http://id.nii.ac.jp/1291/00009645/ departmental bulletin paper